Cybersecurity Gets Smart. - Greengard, Samuel (Communications of the ACM, 2016)
The article reports on the initiatives of researchers to apply artificial intelligence and machine learning methods to improve cybersecurity. It discusses security breaches and cyber protection schemes and highlights the security software introduced by Deep Instinct that uses artificial neural network to digest data and put it into use. Other AI projects cited include the use of algorithm that analyzes relationships with peer files, and use of touch signature to authenticate a mobile device.